Voltage loss breakdown in desalination fuel cells - Salman Abdalla; Shada Abu Khalla; Matthew E. Suss (Electrochemistry Communications, 2021)
The desalination fuel cell (DFC) is a novel technology for co-production of electricity and desalinated water from a clean energy source, the H2/O2 redox couple. A DFC utilizes a fuel cell anode and cathode to catalyze the chemical-to-electrical energy conversion, as well as a cation and anion exchange membrane to desalinate the feedwater flowing through the cell. To identify key bottlenecks in this nascent technology, it is important to quantify voltage losses associated with major elements of the cell. We here provide first-time detailed experimental breakdowns of voltage losses at electrodes and across membranes in a custom-built DFC, operated both with near-neutral pH water streams and in a pH-gradient mode. The results allow us to pinpoint sources of major voltage losses, provide hypothesis for underlying causes, and can serve to focus future DFC materials development and cell engineering efforts.